Formulasi dan Uji Aktivitas Gel Anti Jerawat Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa bilimbi Linn): Formulation and Activity Test of Anti Acne Gel Ethanol Contained Extract of Starfruit Leaves (Averrhoa bilimbi Linn) - Akhmad Ifda Hanip; Dewi Mayasari; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Averrhoa bilimbi Linn is a plant that is used by the local community as an itchy and acne remedy. Secondary metabolite content of ethanol extract of Starfruit leaves (Averrhoa bilimbi Linn) can inhibit the growth of acne bacteria. The purpose of this study was to determine the best concentration in the manufacture of anti-acne gel formulations of ethanol extract of Starfruit leaves (Averrhoa bilimbi Linn) using HPMC base. Extract concentrations were made of 5%, 7.5%, and 10%. After antibacterial tests, the extract concentration used was 7.5% with a inhibition zone of 11.17 mm P.acnes bacteria and 11.30 mm S.aureus bacteria. Anti-acne gel ethanol extract of starfruit leaves (Averrhoa bilimbi Linn) made 3 replication formulas with extract levels FR1 (7.5%), FR2 (7.5%) and FR3 (7.5%). The results showed that the color of the dark green preparation, distinctive smell, thick, no syneresis, ph 4.7-6.2, scatter power 4.6-5.2 cm, clinginess 6-22 seconds and viscosity of 11-20 Pa.s. Antibacterial activity tests on P.acnes showed a inhibition zone of 10.1-10.73 mm and S.aureus showed a inhibition zone of 10.35-10.93 mm. So, it was concluded that the formulation of anti-acne gel was able to inhibit the growth of P.acnes and S.aureus bacteria and meet physical characteristics.